A Review of Fibre Reinforced Polymer Structures - Jawed Qureshi (Fibers, 2022)
This paper reviews Fibre Reinforced Polymer (FRP) composites in Civil Engineering applications. Three FRP types are used in Structural Engineering: FRP profiles for new construction, FRP rebars and FRP strengthening systems. Basic materials (fibres and resins), manufacturing processes and material properties are discussed. The focus of the paper is on all-FRP new-build structures and their joints. All-FRP structures use pultruded FRP profiles. Their connections and joints use bolting, bonding or a combination of both. For plate-to-pate connections, effects of geometry, fibre direction, type and rate of loading, bolt torque and bolt hole clearance, and washers on failure modes and strength are reviewed. FRP beam-columns joints are also reviewed. The joints are divided into five categories: web cleated, web and flange cleated, high strength, plate bolted and box profile joints. The effect of both static and cyclic loading on joints is studied. The joints’ failure modes are also discussed.